Studi Kontribusi Career Exploration terhadap Work Readiness pada Fresh Graduate di Kota Bandung - Adelia Noviyanti; Dinda Dwarawati (UNISBA Press, 2023)
Abstract. The purpose of this study was to determine how much career exploration contributes to work readiness in fresh graduates in Bandung City. According to Caballero and Walker (2010) work readiness is the extent to which graduates have the skills and qualities that make them ready for success in the workplace. According to Stumpf et al., (1983) career exploration is behavior aimed at obtaining information about work or organizations. The subjects of this study were 197 fresh graduates in Bandung City. The hypothesis of this study is that career exploration contributes significantly to work readiness in fresh graduates in Bandung City. The method used is quantitative, causality design with simple regression analysis. The measuring instrument used is the Career exploration Survey (CES) developed by Stumpf et al. (1983) and adapted into Indonesian by Preston and Salim (2019). The work readiness measuring instrument uses the work readiness scale (WRS) developed by Caballero and Walker (2010) and has been adapted and modified into Indonesian by Wijayanti (2019). The results showed 63% of fresh graduates had high career exploration and 60% had a high level of work readiness. The results of regression analysis show an R Square value of 0.564, so it can be said that career exploration contributes 56.4% to work readiness in fresh graduates in Bandung City. Abstrak. Tujuan penelitian ini adalah untuk mengetahui seberapa besar kontribusi career exploration terhadap work readiness pada fresh graduate di Kota Bandung. Menurut Caballero dan Walker (2010) work readiness merupakan sejauh mana lulusan memiliki keterampilan dan kualitas yang membuat siap untuk sukses di tempat kerja. Menurut Stumpf et al., (1983) career exploration adalah perilaku yang ditujukan untuk memperoleh informasi mengenai pekerjaan atau organisasi. Subjek penelitian ini yaitu 197 fresh graduate di Kota Bandung. Hipotesis penelitian ini yaitu career exploration berkontribusi secara signifikan terhadap work readiness pada fresh graduate di Kota Bandung. Metode yang digunakan yaitu kuantitatif, desain kausalitas dengan analisis regresi sederhana. Alat ukur yang digunakan yaitu Career exploration Survey (CES) yang dikembangkan oleh Stumpf et al. (1983) dan diadaptasi kedalam bahasa indonesia oleh Preston dan Salim (2019). Alat ukur work readiness menggunakan work readiness scale (WRS) yang dikembangkan oleh Caballero dan Walker (2010) dan telah diadaptasi dan dimodifikasi kedalam bahasa Indonesia oleh Wijayanti (2019). Hasil penelitian menunjukkan 63% fresh graduate memiliki career exploration yang tinggi dan 60% memiliki tingkat work readiness yang tinggi. Hasil analisis regresi menunjukkan nilai R Square 0,564, sehingga dapat dikatakan Career exploration memberikan kontribusi sebanyak 56.4% terhadap work readiness pada fresh graduate di Kota Bandung.